Pengaruh Sistem Akuntansi Penjualan Kredit dan Penagihan Piutang Terhadap Pengendalian Intern Piutang Tak Tertagih Pada Perum Perumnas Regional 1 Medan - Rama Dani; Retnawati Siregar (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
This study aims to determine whether the credit sales accounting system and accounts receivable collection accounting system partially affect the internal control of uncollectible accounts at Perum Perumnas Regional 1 Medan. This type of research uses quantitative methods. The population in this study were all manager assistant managers and employees at Perum Perumnas Regional 1 Medan as many as 150 people. Sampling based on a purposive sampling approach, the sample in this study is all managers, assistant managers, employees of marketing and sales, and employees of the finance department as many as 30 people. The data analysis technique used is descriptive statistics. Tests were carried out by testing data quality, namely validity and reliability tests, classical assumption tests, namely normality tests, multicollinearity tests, and heteroscedasticity tests, multiple linear analysis tests, and hypothesis testing, namely partial test (t test) and determination coefficient test (r2). using the SPSS application version 24. The results of this study indicate that the credit sales accounting system has a positive and significant effect on the internal control of bad debts and the collection accounting system has a positive and significant effect on the internal control for uncollectible accounts at Perum Perumnas Regional 1 Medan.